CIA. Molinera La Encantada - Mendiola, Alfredo; Villanes, Liz (Universidad ESAN. ESAN Ediciones, 2004)
The present case raises the general situation of a hypothetical company well positioned in the market and that apparently operates efficiently. The focus is on the short-term financial management policy that, at first glance, does not seem to present major drawbacks. However, in-depth analysis can lead to different conclusions.

El presente caso plantea la situación general de una empresa hipotética bien posicionada en el mercado y que opera, aparentemente, con eficiencia. La atención se centra en la política de gestión financiera de corto plazo que, a primera vista, no parece presentar mayores inconvenientes. Sin embargo, un análisis profundo puede llevar a conclusiones diferentes.
Keywords: Business management; Administración de empresas; Financial management|Case studies; Gestión financiera; Estudios de casos; Peru; Perú; https://purl.org/pe-repo/ocde/ford#5.02.04